2006
DOI: 10.1103/physrevd.74.044022
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phantom cosmology

Abstract: We apply the formalism of quantum cosmology to models containing a phantom field. Three models are discussed explicitly: a toy model, a model with an exponential phantom potential, and a model with phantom field accompanied by a negative cosmological constant. In all these cases we calculate the classical trajectories in configuration space and give solutions to the Wheeler-DeWitt equation in quantum cosmology. In the cases of the toy model and the model with exponential potential we are able to solve the Whee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(167 citation statements)
references
References 78 publications
2
162
3
Order By: Relevance
“…The classical singular asymptotic behaviour of these dark energy models has led to a quantum cosmological analysis of these setups [39][40][41][42]95]. In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip.…”
Section: Introductionmentioning
confidence: 99%
“…The classical singular asymptotic behaviour of these dark energy models has led to a quantum cosmological analysis of these setups [39][40][41][42]95]. In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip.…”
Section: Introductionmentioning
confidence: 99%
“…and for the big-rip singularity occuring at large scale factor, [15]. The big-rip singularity is a singularity which the universe can encounter when it ex-pands "too rapidly" [16].…”
Section: Introductionmentioning
confidence: 99%
“…Later on this duality was generalized into more complicated DE models, where it has been shown to exist too [166,167,168,169,170,171]. In [172,173] the authors have studied this cosmic duality and its connection to the fates of the universe, while in [174] the author has also discussed the possibility of realizing the aforementioned duality in braneworld cosmological paradigm. A common feature of these studies is that the EoS parameter does not cross −1.…”
Section: Cosmic Dualitymentioning
confidence: 99%